Rancang Bangun Sistem Layanan Sosial Terpadu Menggunakan Metode Rapid Application Development pada Dinas Sosial Kabupaten Banyuasin - Rahmi Hidayati; Tata Sutabri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Fast, accurate, and transparent social services are essential to supporting community welfare. However, the social service process at the Banyuasin Regency Social Service still faces various obstacles due to suboptimal data processing, information delays, and a lack of integration between service areas. This study aims to design and build a web-based integrated social service system at the Banyuasin Regency Social Service to address the problem of unintegrated and manual data management. The method used is Rapid Application Development (RAD) because it can accelerate the development process through an iterative approach and direct user involvement. The developed system includes several features such as data collection on families receiving social assistance, data collection on people with disabilities, data collection on disaster victims, and reporting. The results of the study indicate that the system has been successfully developed to the prototype stage and tested using the black-box testing method on 12 main modules. The test results indicate that all system functions run as expected without any significant errors. With this system, it is hoped that the Banyuasin Regency Social Service can provide more responsive and accountable services.